Screening of factors influencing dilute nitric acid pretreatment for xylan recovery from oil palm frond bagasse - Nurul Aishah, Mazlan; Kamaliah, Abdul Samad; Rozaimi, Abu Samah; Hafizuddin, Wan Yussof (IOP Publishing, 2020)
Lignocellulosic biomass is the most abundant biodegradable material that has been used in obtaining various of valuable products. However, the conversion may hinder due to its solvent insoluble characteristic which can be treated by nitric acid pretreatment. Therefore, the present study aimed to investigate the effect of nitric acid pretreatment on oil palm frond bagasse (OPFB) for achieving high xylan recovery. A two-level factorial design was employed to determine the best condition for the process. The result revealed that the sequence of contribution effect toward the increment of xylan recovery was found to be temperature > solid loading > reaction time > acid concentration > agitation. Pretreatment of OPFB with nitric acid discovered the temperature of 37 °C with 5% solid loading at 0.01% acid concentration for 24 hours without agitation were determined as the best condition to recover up to 27.63% of xylan. The present results highlight that nitric acid pretreatment has the potential to improve xylan recovery by removing lignin to facilitate enzymatic hydrolysis for product recovery.